Blockade of tumor cell-intrinsic PD-L1 signaling enhances AURKA-targeted therapy in triple negative breast cancer - Takchi, Andrew; Zhang, Minzhi; Jalalirad, Mohammad; Ferre, Roberto Leon; Shrestha, Royal; Haddad, Tufia; Sarkaria, Jann; Tuma, Ann; Carter, Jodi; David, Hillman; Giridhar, Karthik; Wang, Liewei; et al. (Frontiers in Oncology, 2024)
Triple negative breast cancer (TNBC) accounts for 15-20% of all breast cancers and mainly affects pre-menopausal and minority women. Because of the lack of ER, PR or HER2 expression in TNBC, there are limited options for tailored therapies. While TNBCs respond initially to standard of care chemotherapy, tumor recurrence commonly occurs within 1 to 3 years post-chemotherapy and is associated with early organ metastasis and a high incidence of mortality. One of the major mechanisms responsible for drug resistance and emergence of organ metastasis is activation of epithelial to mesenchymal transition (EMT) reprogramming. EMT-mediated cancer cell plasticity also promotes the enrichment of cancer cells with a CD44 high /CD24 low and/or ALDH high cancer stemlike phenotype [cancer stem cells (CSCs)], characterized by an increased capacity for tumor self-renewal, intrinsic drug resistance, immune evasion and metastasis. In this study we demonstrate for the first time a positive feedback loop between AURKA and intra-tumoral PD-L1 oncogenic pathways in TNBC. Genetic targeting of intra-tumoral PD-L1 expression impairs the enrichment of ALDH high CSCs and enhances the therapeutic efficacy of AURKA-targeted therapy. Moreover, dual AURKA and PD-L1 pharmacological blockade resulted in the strongest inhibition of tumor growth and organ metastatic burden. Taken together, our findings provide a compelling preclinical rationale for the development of novel combinatorial therapeutic strategies aimed to inhibit cancer cell plasticity, immune evasion capacity and organ metastasis in patients with advanced TNBC.